Developing of Listening Materials at the Tenth Grade Students - Syaprizal Syaprizal; Agus Triyogo; Ratna Nirwana (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aims to develop listening material for tenth graders. The research method used is Research and Development (R&D). The results of this study indicate that the development of listening material is valid, practical and effective in the teaching and learning process. The product developed was declared valid after being evaluated by three experts with an average score of 3.86 in the "high" category. This product is also practical by evaluating listening material for students with an average score of 4.10 with "high practicality" and effective with an evaluation with 83.33 students in the "high" category. In conclusion, the listening material developed for tenth-grade students of Islamic Senior High School 2 Lubuklinggau is valid, practical and effective categories. Keywords: Listening, Materials, Research and Development